Commercial marine fish species from Weh Island, Indonesia: Checklist, distribution pattern and conservation status (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Zulfahmi I, Apriansyah M, Batubara AS, Kautsari N, Sumon KA, Rahman MM, Nur FM. 2022. Commercial marine fish species from Weh Island, Indonesia: Checklist, distribution pattern and conservation status. Biodiversitas 23: 1977-1989. In this study, we first report a systematic checklist of commercial marine fish species from Weh Island, Indonesia, including notes on their distribution pattern, conservation status, and commercial value. Fish sampling was conducted at three major fish markets in Weh Island, and these specifically were Cangkoan Fish Market, Kuta Timu Fish Market, and Balohan Fish Market. A total of 50 fish species belonging to 8 orders and 24 families were documented. Carangidae (12%, 6 species) was the predominant family, followed by the Scaridae (10%, 5 species) and other families (78%, 22 families, 39 species). Based on the IUCN red list, commercial marine fish species in Weh Island were dominated by the "Least Concern" category (78%, 39 species), followed by the "Not Evaluated" (14%, 7 species), the "Near Threatened" (4%, 2 species), and the "Data Deficient" (4%, 2 species). The market price of the fish ranged from 0.34 USD/kg to 6.19 USD/kg, with three fish families included in the high commercial value, namely the Clupeidae, Carcharhinidae, and Serranidae.
Keywords: Carangidae, distribution pattern, fish market, high commercial value, least concern category